The Effect of Reading Aloud on the Listening Ability of Fifth-Grade Students - Zamago, Dirman Yanto; Gea, Fersi; Gulo, Lady Friska; Waruwu, Faef Mei Adaria; Ndruru, Clara Sinte Olivia; Zamasi, Alvin Ebenezer; Telaumbanua, Yasminar Amaerita (UIBU, 2026)
Listening was an essential language skill that supports learners in understanding spoken English. However, many elementary students experience difficulties in listening comprehension because of limited exposure to meaningful spoken input. This study investigated the effect of Reading Aloud on the listening ability of fifth-grade students. A quantitative approach using a quasi-experimental one-group pretest–posttest design was employed with 24 fifth-grade students at UPTD SD Negeri 070978 Gunungsitoli. Data were collected using a researcher-developed 20-item multiple-choice listening test and analyzed using descriptive statistics, the Shapiro–Wilk normality test, and a paired-samples t-test. The mean score increased from 41.46 on the pre-test to 70.42 on the post-test. The paired-samples t-test showed a significant improvement in students' listening ability, t(23) = -24.861, p < .001. These findings indicate that Reading Aloud is an effective instructional strategy for improving elementary students' listening ability. However, because this study employed a one-group pretest–posttest design, future research should include a control group and a larger sample to enhance the validity and generalizability of the findings.